'State-maintaining' causatives: A close kin to resultatives. (November 2017) - Iwata, Seizi
Abstract: The aim of this paper is to demonstrate that expressions like hold – open (e.g. I held the door open ), tape – shut (e.g. He taped the door shut ), and lock – in the bathroom (e.g. Harry locked Joe in the bathroom ), which look like resultatives, are actually not resultatives, and that these expressions can be accommodated as instances of 'state-maintaining' causatives in a theory building upon Talmy's (2000) force dynamics. Furthermore, the proposed analysis gives us an insight into how the expression keep – from (e.g. Harry kept Joe from moving out of the bathroom ) is motivated. Highlights: 'State-maintaining' causatives, as distinct from resultatives, need to be recognized. Some apparent resultatives should be analyzed as instances of 'state-maintaining' causatives. A new light is shed on what from means in keep – from (e.g. Harry kept Joe from moving out of the bathroom ).